Churches were centrally planned in Syria during the byzantine period (Damascus University Journal of Historical Studies, 2025)
The researcher counted the most important churches with central planning in Syria, and explained the differences between them in terms of planning and various architectural elements. It appears that central planning was an architectural solution for churches that contain one of the shrines of martyrs to organize the movement of pilgrims to the church. It also provided a solution to the preaching process in this early period. Especially with the difficulty of believers hearing the preacher in basilican churches.
Keywords: Church; Apse; Architecture; Byzantine; Central Planning